2014
DOI: 10.1111/1574-6941.12438
|View full text |Cite
|
Sign up to set email alerts
|

Diazotrophic potential among bacterial communities associated with wild and cultivatedAgavespecies

Abstract: Agaves are major biotic resources in arid and semi-arid ecosystems. Despite their ecological, economical and cultural relevance, many aspects of the microbial communities associated with agaves are still unknown. Here, we investigated the bacterial communities associated with two Agave species by 16S rRNA- Denaturing gradient gel electrophoresis fingerprinting and sequencing. We also evaluated the effects of biotic and abiotic factors in the structure of the bacterial communities. In parallel, we isolated and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
71
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 66 publications
10
71
0
Order By: Relevance
“…We verified the effectiveness of the surface sterilization protocol by two different methods (see Materials and Methods) indicating that the protocol used is sufficient for the surface sterilization of plant tissues. Another caveat of this work and other studies on plant-associated microbial communities (Desgarennes et al, 2014; Coleman-Derr et al, 2016) is the use of different DNA extraction kits depending on the sample type. This can be explained by the fact that the DNA kits are not equally suited for different starting materials and the respective contaminations.…”
Section: Resultsmentioning
confidence: 99%
“…We verified the effectiveness of the surface sterilization protocol by two different methods (see Materials and Methods) indicating that the protocol used is sufficient for the surface sterilization of plant tissues. Another caveat of this work and other studies on plant-associated microbial communities (Desgarennes et al, 2014; Coleman-Derr et al, 2016) is the use of different DNA extraction kits depending on the sample type. This can be explained by the fact that the DNA kits are not equally suited for different starting materials and the respective contaminations.…”
Section: Resultsmentioning
confidence: 99%
“…This study determined that prokaryotic communities associated with agaves were chiefly influenced by the sample type or plant compartment, where the rhizosphere, the phyllosphere and the root and leaf endosphere were clearly distinct from one another and also from the surrounding soils. These results were previously suggested for agaves (Desgarennes et al ., ), but by using next‐generation sequencing (NGS), these differences were made more clear even among epiphytic groups. Moreover, by including a Californian species, A. deserti , living > 2000 km apart from A. tequilana and A. salmiana , our data revealed the convergence of prokaryotic communities in Agave , regardless of cultivation status and biogeography.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were prepared and total DNA was extracted as previously described (Desgarennes et al ., ). For amplification of the ITS2 and 16S regions, we used the ITS9F/ITS4R and 515F/816R primer pairs, respectively, and followed the PCR protocol described in the Supporting Information.…”
Section: Methodsmentioning
confidence: 97%
“…robusta , and M . geometrizans (Desgarennes et al, ; Fonseca‐García et al, ) were used in this study (Table S1). These strains include core and representative members of the microbiome of agaves and cacti (Figure S1) from the phyla Actinobacteria (5 spp.…”
Section: Methodsmentioning
confidence: 99%
“…Recent research revealed the microbiome composition, diversity, and assembly rules of five plant species endemic to the drylands of Central and North America, namely, Agave tequilana , which is grown and used for tequila production, and native Agave deserti , Agave salmiana , Myrtillocactus geometrizans , and Opuntia robusta (Coleman‐Derr et al, ; Desgarennes, Garrido, Torres‐Gomez, Peña‐Cabriales, & Partida‐Martinez, ; Fonseca‐García et al, ). These species belong to two taxonomically unrelated but ecologically and economically important plant families: the Asparagaceae and the Cactaceae.…”
Section: Introductionmentioning
confidence: 99%